Addendum and corrigendum to "On the chaos game of iterated function systems" - Barrientos, Pablo G.; Fitzsimmons, Maxwell; Ghane, Fatemeh H.; Malicet, Dominique; Sarizadeh, Aliasghar (Topological Methods in Nonlinear Analysis, 2020)
We provide a counter-example to Theorem 1.4(a) in Topol. Methods Nonlinear Anal. 49 (2017), no. 1, 105-132, by showing that the closure of the Γ-orbit of a point x in the pointwise basin of Ls-attraction of a quasi-attractor A is not compact. In order to fix this gap, we modified the definition of Ls-basin of attraction. In addiction, we propose a better place to play the chaos game and as a consequence we get some additional results on strongly-fibred quasi-attractors and Conley attractors.